Study of Power Consumption and Current Efficiency for the Production of Sodium Hypochlorite in an Electrolytic Cell - Aziz, MA; Rahman, MS; Ali, MS; Islam, MM (Journal of Chemical Engineering, 2010)
Journal of Chemical Engineering Vol.ChE 23 1995-2005